Sustainable public procurement in public higher education institutions: basic principles and the need for their implementation - O.A. Pylypchuk (Економіка, управління та адміністрування)
Today, when the whole humanity must confront the global environmental challenges facing society, it is necessary to introduce new technologies in all areas of activity that will help ensure the preservation of the planet’s ecology. First and foremost, such innovations should start with the areas where the state has direct influence, so that it can control all these processes. In turn, one of the areas where such changes can have a significant impact on the environment is the public procurement system. This is because it is through the public procurement system that the necessary needs of the state (and state / utility enterprises in particular) are planned and ways to meet these needs are sought. In fact, the entire provision of the state with the necessary resources is carried out through the public procurement system, and hence a change in the approach to the selection of procurement criteria may help reduce the negative impact on the environment. Sustainable public procurement (SPP) was created to reduce the negative impact on the ecological system. Such procurement is also known as green procurement, one of the goals of which is to reduce the environmental impact. The role of state higher education institutions (SHEIs), which not only form a new generation of specialists but also have a significant impact on the country’s economy and environment, will be particularly important in the development of a sustainable public procurement system in Ukraine. Integration of SPP into the activities of higher education institutions can ensure not only economic efficiency, but also lead to improvement of the environmental situation and raise awareness of students and teachers about sustainable development. In turn, this will allow training more experienced professionals in this field, who will be able to further improve the SPP system in the future. Nevertheless, in order to implement a system of sustainable public procurement in public higher education institutions, it is necessary to clearly understand what such procurement is. It is also necessary to understand what difficulties may be encountered during their implementation and how to cope with them. This article will discuss sustainable public procurement, what it includes, the need for its implementation in public higher education institutions, the benefits, as well as potential challenges that may arise during its implementation and potential ways to overcome them.